Comprehensive comparison on optical properties of samarium oxide (micro/nano) particles doped tellurite glass for optoelectronics applications - M. N., Azlan; Saleh, Hajer Saad; Mohamed Kamari, Halimah; S. A., Umar; Mohd Zaid, Mohd Hafiz; R., Hisam; S. M., Iskandar; B. K., Kenzhaliyev; G. K., Kassymova; N. N., Yusof (Springer, 2021)
Rare-earth oxides microparticles doped tellurite-based glass have been studied extensively to improve the capability of optoelectronic devices. We report a detailed comparison between two sets of glass series containing samarium microparticles and nanoparticles denoted as ZBTSm-MPs and ZBTSm-NPs, respectively. The two sets of glass have been successfully fabricated via meltquenching technique with chemical formula {[(TeO2)0.70 (B2O3)0.30]0.7 (ZnO)0.3}1-y (Sm2O3 (MPs/NPs))y with y = 0.005, 0.01, 0.02, 0.03, 0.04 and 0.05 mol fraction. The TEM analysis confirmed the existence and formation of nanoparticles in ZBTSm-NPs glasses. The density of ZBTSm-NPs glasses was found higher than ZBTSm-MPs glasses due to the distributions of nano-scale particles in tellurite glass network. There was a linear trend of increment in the refractive index in both sets of glass series along with the concentrations of dopants. The refractive index of ZBTSm-NPs glasses was found higher than ZBTSm-MPs glasses due to the shift in compactness of glass structure with nano-scale particles. In comparison, the absorption peaks of ZBTSm-MPs glasses were greater than ZBTSm-NPs glasses which were mainly due to the restriction of electrons mobility in glass network with nano-scale particles. The optical band gap energy in ZBTSm-NPs glasses was found greater than ZBTSm-MPs glasses which correspond to the widening of forbidden gap with nano-scale particles. The polarizability of ZBTSm-NPs and ZBTSm-MPs was found in nonlinear trends along with dopant concentrations. Based on these findings, the improvement of optical properties has been made by introducing samarium oxide nanoparticles in tellurite glass which is beneficial for optoelectronic devices.